Regulation of Translational Efficiency by Disparate <svg style="vertical-align:-0.216pt;width:16.1625px;" id="M1" height="23.575001" version="1.1" viewBox="0 0 16.1625 23.575001" width="16.1625" xmlns:xlink="http://www.w3.org/1999/xlink" xmlns="http://www.w3.org/2000/svg"> <g transform="matrix(.022,-0,0,-.022,.062,23.25)"><path id="x35" d="M153 550l-26 -186q79 31 111 31q90 0 141.5 -51t51.5 -119q0 -93 -89 -166q-85 -69 -173 -71q-32 0 -61.5 11.5t-41.5 23.5q-18 17 -17 34q2 16 22 33q14 9 26 -1q61 -50 124 -50q60 0 93 43.5t33 104.5q0 69 -41.5 110t-121.5 41q-53 0 -102 -20l38 305h286l6 -8 l-26 -65h-233z" /></g> <g transform="matrix(.016,-0,0,-.016,10.825,12.488)"><path id="x2032" d="M227 744l-123 -338l-31 15l73 368q12 3 41.5 -8t36.5 -20z" /></g> -UTRs of PPAR<svg style="vertical-align:-4.698pt;width:11.35px;" id="M2" height="16.012501" version="1.1" viewBox="0 0 11.35 16.012501" width="11.35" xmlns:xlink="http://www.w3.org/1999/xlink" xmlns="http://www.w3.org/2000/svg"> <g transform="matrix(.022,-0,0,-.022,.062,10.1)"><path id="x1D6FE" d="M478 372q0 -39 -31 -97t-61 -98t-78 -98q-45 -55 -73 -102q-13 -79 -13 -197q-11 -11 -43.5 -25.5t-53.5 -15.5l-15 17q5 35 26 101.5t47 123.5q8 72 -1.5 174.5t-37.5 178.5q-14 37 -29 37q-20 0 -67 -65l-25 21q37 60 73 90.5t63 30.5q47 0 72 -112q13 -56 17.5 -141.5 t0.5 -143.5h2q155 193 155 297q0 26 -12 47q-5 8 -5 15q0 16 12.5 27t29.5 11q21 0 34 -21t13 -55z" /></g> Splice Variants - McClelland, Shawn; Shrivastava, Roopali; Medh, Jheem D. (PPAR Research, 2009)
The PPAR-γ gene encodes for at least 7 unique transcripts due to alternative splicing of five exons in the 5′-untranslated region (UTR). The translated region is encoded by exons 1–6, which are identical in all isoforms. This study investigated the role of the 5′-UTR in regulating the efficiency with which the message is translated to protein. A coupled in vitro transcription-translation assay demonstrated that PPAR-γ1, -γ2, and -γ5 are efficiently translated, whereas PPAR-γ4 and -γ7 are poorly translated. An in vivo reporter gene assay using each 5′-UTR upstream of the firefly luciferase gene showed that the 5′-UTRs for PPAR-γ1, -γ2, and -γ4 enhanced translation, whereas the 5′-UTRs for PPAR-γ5 and -γ7 inhibited translation. Models of RNA secondary structure, obtained by the mfold software, were used to explain the mechanism of regulation by each 5′-UTR. In general, it was found that the translational efficiency was inversely correlated with the stability of the mRNA secondary structure, the presence of base-pairing in the consensus Kozak sequence, the number of start codons in the 5′-UTR, and the length of the 5′-UTR. A better understanding of posttranscriptional regulation of translation will allow modulation of protein levels without altering transcription.